Treatment of Multiple Sclerosis With Teriflunomide. Multicenter Study of Real Clinical Practice in the Valencian Community-Spain - Lamberto Landete (Frontiers Media S.A., 2021)
Introduction: We have different treatment alternatives for relapsing-remitting multiple sclerosis–RRMS–within the so-called platform drugs. It would be desirable to know the ideal drug for each patient. Real clinical practice studies provide us with data on drug efficacy in the medium and long term, safety beyond clinical trials, and can help us to know the patient profile appropriate for each therapy.Material and Methods: An observational multicenter study of real clinical practice in patients with RRMS who were treated with teriflunomide in the Valencian Community, since teriflunomide was authorized in Spain. The database created for this study collects retrospectively patients followed prospectively in the MS clinics.Objectives: To analyze the efficacy and safety of teriflunomide treatment in patients with RRMS under the conditions of real clinical practice, and to identify a patient profile responding to the treatment.Results: We obtained data from 340 patients who received at least one dose of 14 mg teriflunomide. The patients were 69.4% female to 30.6% male, had a mean age of 46.4 years, and a mean time of progression of MS of 11.5 years. The mean pre-teriflunomide relapse rate was 0.4 years, the mean EDSS scorewas 1.98, IgG Oligoclonal bands were present in the CSF of 66.2% of the patients, IgM Oligoclonal bands were present in 46.9%, and the mean number of gadolinium-enhancing lesions was 1.07 lesions per patient at the beginning of treatment. The average number of treatments previously received was 1.04, and 28.53% were naïve. After a follow-up of up to 4 years, a reduction in the annualized and cumulative annualized relapse rate was observed in the first year, in the second year, and in the third year, compared to the pre-treatment year. The EDSS scores were stabilized throughout the follow-up. Likewise, there was a reduction in gadolinium-enhancing lesions in the 1st and 2nd years compared to the pre-treatment period. Applying different generalized multiple linear regression models, we identified a profile of a responding patient to teriflunomide as a male without IgM oligoclonal bands in the CSF, a previous EDSS score of <3, and more than 5 years duration of MS.